Spatial and temporal plant phenological niche differentiation in the Wadi Degla desert ecosystem (Egypt) - Hegazy, Ahmad; Alatar, Abdelrahman A.; Lovett-Doust, Jon; El-Adawy, Hosam A. (Acta Botanica Croatica, 2012)
Twenty dominant plant species representing different life forms were investigated phenologically over a period of 36 months (January 2004 to December 2006). Plant populations were sampled at down-, mid-, and upstream sites in a desert wadi ecosystem. The results were analyzed using TWINSPAN, DCA and CCA techniques. Five phenological niches were apparent: (1) species flowering all year round, with peaks in spring and autumn such as Ochradenus baccatus; (2) species flowering during winter including Lycium shawii and Tamarix nilotica; (3) species flowering during spring, e.g., Zilla spinosa, Zygophyllum coccineum and Capparis spinosa; (4) species flowering during summer including Iphiona mucronata and Deverra triradiata; and (5) species flowering during autumn that include Atriplex halimus and two Anabasis species. The climatic variables, including temperature, rainfall and relative humidity, affect the phenological niches and between-species differences. Within-species variations occurred between years and there were no between-site variations for most study species. The different plant species exhibited phenological diversity along the course of the wadi ecosystem. The phenological niches are species-specific and environmentally dependent rather than local selective pressures.